Histone H3 Lysine 9 Acetylation Plays a Role in Adipogenesis of Periodontal Ligament-Derived Stem Cells - Julio A. Montero-Del-Toro; Angelica A. Serralta-Interian; Geovanny I. Nic-Can; Mónica Lamas; Rodrigo A. Rivera-Solís; Beatriz A. Rodas-Junco (Epigenomes)
Background: The epigenetic regulation of adipogenic differentiation in dental stem cells (DSCs) remains poorly understood, as research has prioritized osteogenic differentiation for dental applications. However, elucidating these mechanisms could enable novel regenerative strategies for soft tissue engineering. Periodontal ligament stem cells (PDLSCs) exhibit notable adipogenic potential, possibly linked to histone 3 acetylation at lysine 9 (H3K9ac); however, the mechanistic role of this modification remains unclear. Methods: To address this gap, we investigated how histone deacetylase inhibitors (HDACis)—valproic acid (VPA, 8 mM) and trichostatin A (TSA, 100 nM)—modulate H3K9ac dynamics, adipogenic gene expression (C/EBPβ and PPARγ-2), and chromatin remodeling during PDLSCs differentiation. Techniques used included quantitative PCR (qPCR), lipid droplet analysis, and chromatin immunoprecipitation followed by qPCR (ChIP-qPCR). Results: TSA-treated cells exhibited increased lipid deposition with smaller lipid droplets compared to VPA-treated cells. Global H3K9ac levels correlated positively with adipogenic progression. VPA induced early upregulation of C/EBPβ and PPARγ-2 (day 7), whereas TSA triggered a delayed but stronger PPARγ-2 expression. ChIP-qPCR analysis revealed significant H3K9ac enrichment at the PPARγ-2 promoter in TSA-treated cells, indicating enhanced chromatin accessibility. Conclusions: These findings demonstrate that H3K9ac-mediated epigenetic remodeling plays a critical role in the adipogenic differentiation of PDLSCs and identifies TSA as a potential tool for modulating this process.